2018
DOI: 10.1111/dme.13707
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic status and depressive symptoms among adults in Germany: results from the German Health Interview and Examination Survey for Adults (DEGS1)

Abstract: Diagnosed diabetes, but not prediabetes, undiagnosed diabetes or HbA , was associated with depressive symptoms among adults in Germany. Studies examining psychosocial and biological mechanisms that may potentially explain relationships between diagnosed diabetes and depressive symptoms are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
11
1
1
Order By: Relevance
“…Similar results have been described in other chronic diseases. In patients with diagnosis of diabetes, depressive symptoms have been reported to be elevated [26] and generic QoL was estimated as good [27]. Nevertheless, patients with diabetes stated that the disease itself has substantial impact on their QoL [27], a result that was not found in our cohort of patients with PKU.…”
Section: Discussioncontrasting
confidence: 57%
“…Similar results have been described in other chronic diseases. In patients with diagnosis of diabetes, depressive symptoms have been reported to be elevated [26] and generic QoL was estimated as good [27]. Nevertheless, patients with diabetes stated that the disease itself has substantial impact on their QoL [27], a result that was not found in our cohort of patients with PKU.…”
Section: Discussioncontrasting
confidence: 57%
“…As previously reported, depressive symptoms were associated with diagnosed but not with undiagnosed T2D in our national health survey dataset. 33 Overall, >90% of the population in Germany see a doctor in office practice at least once a year. The present study showed that this does not apply to people with undiagnosed T2D who were significantly less likely to visit a doctor compared with people either with diagnosed T2D or with normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Alcohol use was grouped into three categories none, moderate and risky drinking based on information obtained with food frequency questionnaires. 33 Obesity was defined based on BMI measures ≥30 kg/m 2 . 13 32 Hyperlipidemia was defined as total cholesterol ≥6.2 mmol/L or current use of lipid-lowering drugs (ATC code C10) in combination with a medical history of hyperlipidemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other cross-sectional studies have confirmed this [17,18]. The LifeLines Study, another large study in this area, analysed data from more than 90 000 individuals, including from a diagnostic interview and an assessment of fasting glucose.…”
Section: The Prevalence Of Depression In Diabetesmentioning
confidence: 92%